Effects of Intravenous Dexmedetomidine on Hemodynamic Stability, Sensory and Motor Block, and Postoperative Analgesia in Patients Receiving 0.5% Hyperbaric Bupivacaine Spinal Anesthesia - Chhajed, Gaurav Mahendra (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Spinal anesthesia with 0.5% hyperbaric bupivacaine is widely used in surgical procedures, but its effectiveness can be enhanced by adjuncts that improve block characteristics, provide prolonged analgesia, and minimize adverse effects. Dexmedetomidine, a selective α2- adrenergic agonist, has shown promise in these areas. This study aimed to evaluate the effects of intravenous dexmedetomidine on patients receiving spinal anesthesia with 0.5% hyperbaric bupivacaine. Objective: To assess the impact of intravenous dexmedetomidine on hemodynamic stability, sensory and motor block characteristics, postoperative analgesia, sedation, and adverse effects in patients undergoing spinal anesthesia with 0.5% hyperbaric bupivacaine. Methods: A total of 110 patients undergoing elective surgery under spinal anesthesia were included in this study, conducted at a tertiary care hospital. Patients were randomly assigned to receive either intravenous dexmedetomidine (Group 1, n = 55) or a saline placebo (Group 2, n = 55). Hemodynamic parameters, sensory and motor block characteristics, postoperative analgesia, sedation, and adverse effects were recorded and analyzed. Results: Dexmedetomidine significantly improved hemodynamic stability, with higher mean arterial pressure (80.5 ± 10.2 mmHg) and lower heart rate (65.2 ± 8.7 beats/min) compared to the control group. The onset of sensory and motor blocks was faster in Group 1 (5.3 ± 1.2 minutes and 6.1 ± 1.3 minutes, respectively) compared to Group 2 (6.0 ± 1.5 minutes and 7.2 ± 1.6 minutes). The duration of sensory and motor blocks was also significantly longer in Group 1 (135.5 ± 15.7 minutes and 160.7 ± 17.5 minutes, respectively). Patients in Group 1 required less postoperative analgesia and had a longer time to the first analgesic request (5.2 ± 1.1 hours vs. 3.1 ± 0.9 hours). Adverse effects, including hypotension and bradycardia, were less frequent in the dexmedetomidine group. Conclusion: Intravenous dexmedetomidine enhances the effectiveness of spinal anesthesia with 0.5% hyperbaric bupivacaine by improving hemodynamic stability, prolonging sensory and motor block durations, and reducing postoperative analgesic requirements. Its sedative properties contribute to increased patient comfort with fewer adverse effects, making it a valuable adjunct in spinal anesthesia. Further research is recommended to confirm these findings in larger and more diverse patient populations. Keywords: Dexmedetomidine, spinal anesthesia, hyperbaric bupivacaine, hemodynamic stability, sensory block, motor block, postoperative analgesia, sedation, adverse effects.